2007
DOI: 10.1097/01.ta.0000241145.02748.df
|View full text |Cite
|
Sign up to set email alerts
|

Male Sexual Dysfunction After Pelvic Fracture

Abstract: This study emphasizes that major pelvic trauma may impair sexual function in men. The results demonstrate an objective measurement of ED by the IIEF as well as an extended spectrum of complaints. The IIEF questionnaire might be considered to identify patients that need further medical evaluation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
57
1
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(67 citation statements)
references
References 50 publications
2
57
1
3
Order By: Relevance
“…The underlying causes of sexual dysfunction after pelvic trauma are related to damage to the autonomic nervous, vascular, or erectile tissues [17,18,24,28,44]. Delays in assessment and treatment of erectile dysfunction may result in irreversible morphologic and functional changes to the erectile tissue and venoocclusive mechanism with less satisfactory outcome [17,18,28,44]. We found a correlation between patient-reported subjective severity of sexual and urinary dysfunction, supporting the view that psychologic and emotional issues also may be important [17].…”
Section: Discussionsupporting
confidence: 63%
See 4 more Smart Citations
“…The underlying causes of sexual dysfunction after pelvic trauma are related to damage to the autonomic nervous, vascular, or erectile tissues [17,18,24,28,44]. Delays in assessment and treatment of erectile dysfunction may result in irreversible morphologic and functional changes to the erectile tissue and venoocclusive mechanism with less satisfactory outcome [17,18,28,44]. We found a correlation between patient-reported subjective severity of sexual and urinary dysfunction, supporting the view that psychologic and emotional issues also may be important [17].…”
Section: Discussionsupporting
confidence: 63%
“…However, our findings were LC type injury was least likely and VS type most likely to result in sexual dysfunction, with similar findings for urinary dysfunction. These findings are supported by a previous German study [28] using the Tile classification [40], which reported higher rates of sexual dysfunction in Type B1 than B2 fractures and in Type C than B2 injuries, as well as other studies showing greater instability associated with more sexual complaints and less recovery [16,28,29,34]. However, there are conflicting reports, with other studies finding no apparent relationship of pelvic fracture type and sexual dysfunction in males [25,31] or females [3,9,11].…”
Section: Discussionsupporting
confidence: 50%
See 3 more Smart Citations